Gestão escolar democrática: as distorções entre os discursos e as ações em uma escola dos Anos Iniciais do Ensino Fundamental público luminense - França, Dayane de Sousa Vasconcelos (2023)
This research, linked to the Educational and School Management Research Line of the Graduate Program in Education at the State University of Maranhão (UEMA), presents a reflection on DEMOCRATIC SCHOOL MANAGEMENT. The general objective of the study is to analyze the existing distortions between the discourses and actions of democratic management in the Cecília Meireles Basic School Unit, which includes the stage of the initial years of Elementary School of the Municipal Network of Paço do Lumiar - MA, for the identification of elements that need to be reflected by the school community on the guarantee of the constitutional right to education. It unfolds in the following specific objectives: a) to understand the concepts of school management in the historical context of the Brazilian public school, from the theoreticians of the new school; b) identify, for analysis, the conceptions of democratic management and the legislation that guide it; c) analyze in order to apprehend how the exercise of democratic management in the public elementary school in Luminense takes place; d) elaborate a Continuing Education Course of continued formation in the on-line modality accompanied by certification, with the purpose of directing and improving the development of the educational work of the school community of the researched public institution. We use observation, semi-structured interviews and content analysis guided by Bardin (2015), for the organization and exploration of data obtained by legal provisions to observe existing distortions between democratization mechanisms and everyday school practices; the management profile of the school in the early years of elementary school in the municipality of Paço do Lumiar - MA; how the school community participates in administrative and didactic-pedagogical decisions to guarantee education as a constitutional right; which educational product can be used to strengthen the concept of democratic management for the school community researched in that municipality. In the methodological processes, this research project is anchored in the dialectical method, considering the social and historical aspects, having a descriptive character and with the use of bibliographical, documental, and field study. It is based on theoretical references, such as: Cury (2002); Gadotti (1994); Libâneo (2010, 2014, 2017, 2021); Lück (2000, 2005, 2009, 2010a, 2010b, 2012, 2013, 2017); Paro (2003, 2014, 2016, 2018a, 2018b); among others, to point out concepts and distortions between the discourse and actions related to democratic management in schools that contemplate the initial years of Elementary Education. From the analysis of the testimonies, we found that the school community surveyed feels little participative in school decisions, due to the absence of dialogue, lack of knowledge in the area and lack of time/space for exchange and reflections on educational issues. In this way, the theme is relevant, and inspires thinking about democratic management in addition to providing opportunities for dialogue with members of the school community, but as a need to put discourses into action, considering the sociocultural, economic and technological transformations through which society has experienced historically, in the sense of guaranteeing the constitutional right to quality school education for citizens.